Thompson’s Self-Efficacy in Katherine Anne Porter’s Noon Wine - NIA KURNIA SARI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2017)
Abstract Every person has different state of psyche especially the state of self-efficacy. Self-efficacy is a person’s belief that he has capability to do a particular task. In Noon Wine, Thompson, as the main character, plays a significant role because when interacts with the environment, his self-eficacy leads to his guilt. The aims of this study are to portray Thompson’s self-efficacy in Katherine Anne Porter’s Noon Wine and to reveal the way Thompson’s “L-UR” leads to his guilt. This study is literary study which applies the concept of self-efficacy by Albert Bandura and the concept of guilt by Gershon M. Breslavs. Those concepts are well applied to answer the statement of the problems. Based on four sources of self efficacy by Bandura, Thompson is indicated as low self-efficacy. Thompson who has low self-efficacy, unfortunately, has to interact in unresponsive environment so that based on six factors which influence the subject matter and the duration of guilt by Breslav, Thompson suffers a long-term or chronic guilt caused by his low self-efficacy. Keywords: self-efficacy, guilt, Noon Wine Abstrak Setiap orang memiliki kondisi kejiwaan yang berbeda khususnya kondisi self-efficacy. Self-efficacy adalah kepercayaan seseorang bahwa dirinya memiliki kemampuan untuk menyelesaikan suatu pekerjaan. Dalam Noon Wine, Thompson, sebagai tokoh utama, memainkan peran penting karena ketika berinteraksi dengan lingkungan, Self-efficacy-nya menyebabkan rasa bersalah baginya. Tujuan penelitian ini adalah untuk menggambarkan self-efficacy Thompson dalam novela Noon Wine karya Katherine Anne Porter dan untuk mengungkap bagaimana “L-UR” Thompson menyebabkan rasa bersalah baginya. Penelitian ini adalah penelitian kesusasteraan yang menerapkan konsep self-efficacy dari Albert Bandura dan konsep rasa bersalah dari Gershon M. Breslavs. Konsep-konsep tersebut diterapkan dengan baik untuk menjawab rumusan masalah. Berdasarkan empat sumber self-efficacy dari Bandura, Thompson diindikasikan memiliki self-efficacy rendah. Thompson, yang memiliki self-efficacy rendah, malangnya, harus berinteraksi dalam lingkungan yang apatis sehingga berdasarkan enam faktor yang mempengaruhi pokok permasalahan dan durasi rasa bersalah dari Breslav, Thompson mengalami rasa bersalah jangka panjang atau rasa bersalah kronis yang disebabkan oleh self-efficacy-nya yang rendah. Kata Kunci: self-efficacy, rasa bersalah, Noon Wine